Christmas cottage [videorecording (DVD)] - Kinkade, Thomas, 1958-2012; Padalecki, Jared, 1982-; Harden, Marcia Gay; O'Toole, Peter, 1932-2013; Asner, Edward (Lionsgate, 2008)
Returning from college one Christmas, Thomas Kinkade finds his mother is ready to lose the family cottage to foreclosure. He is inspired to paint a mural of his hometown, which launches his career and helps the town rediscover their Christmas spirit.